Analysis of defuzzification for determining the ranking of green skills - Ismail, Affero; Zaime, Adib Farhan; Lai, Chee Sern; Mohd Zubir, Muhammad Zulfadly; Ibrahim, Badaruddin (2020)
Apart from technical and generic skills, employers start looking for manpower with green skills which are much needed for promoting sustainable development in social, economic as well as environment. This article aimed at finding out the ranking of element of green skills demanded by the green industry based on the experts perspective. A total of 11 experts have been invited to express their experience and knowledge regarding to the green aspects. The Delphi technique has been conducted and comprised three rounds of data collection following a pilot. The fuzzy Delphi analysis method has beenused for analysing the data obtained from the third round of data collection. The defuzzification process has been conducted to measure the score and ranking of green skills. The result shows that the energy and water skill is the most prominent skill within the skill dimension as compared to other green skills. For knowledge and attitude dimensions, the most critical elements are waste management knowledge and awareness respectively.